Sample sizes for non-inferiority studies based on the difference between two proportions: a unified approach for difference, ratio and odds ratio models - Bruno Mario Cesana; Paolo Antonelli (Epidemiology, Biostatistics and Public Health)
Background: It is never easy to make sample size calculation for two-arm, non-inferiority studies with a primary proportion outcome not only because the different parameterisations involved in the difference, ratio, and odds ratio models lead to different non-inferiority margins and different sample size results, but also because of the different efficiency of the respective sample size formulae.